2013
DOI: 10.1177/1367006912454618
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of first language attrition across the lifespan

Abstract: This special issue explores the relevance of Dynamic Systems Theory (henceforth DST) to research in first language attrition (henceforth L1 attrition). While research in L1 attrition has traditionally drawn on paradigms in other areas of linguistic enquiry, e.g. approaches current in L2 acquisition studies, important developments across a range of disciplines have paved the way for a fundamentally different conceptualisation of language development. In this special issue, DST guides our enquiry into L1 attriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
2
Order By: Relevance
“…Although most of the recordings were made in Germany, and the year of the interviews was known, it was not known, for example, at what point the interview was made during her stay in Germany. Such short-term effects of ambient language exposure may have counter-acted or even enhanced any long-term effects, which might have been evidenced had SG returned less frequently to Germany (see de Bot et al, 2007;de Bot & Schrauf, 2010;de Leeuw, Opitz, et al, 2013 in relation to the emphasis on short and long term changes in native speech with regard to Dynamic Systems Theory, as well as Paradis, 2004Paradis, , 2007 in relation to language exposure influencing language production with regard to the Activation Threshold Hypothesis). However, it is likewise possible that the frequency of SG's visits may have made L2 effects on the L1 more likely as it has also been found that interaction may be more prevalent where dual activation occurs commonly (Mora, Keidel, & Flege, 2015), although it is not known how strictly German and English were separated during SG's visits to Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the recordings were made in Germany, and the year of the interviews was known, it was not known, for example, at what point the interview was made during her stay in Germany. Such short-term effects of ambient language exposure may have counter-acted or even enhanced any long-term effects, which might have been evidenced had SG returned less frequently to Germany (see de Bot et al, 2007;de Bot & Schrauf, 2010;de Leeuw, Opitz, et al, 2013 in relation to the emphasis on short and long term changes in native speech with regard to Dynamic Systems Theory, as well as Paradis, 2004Paradis, , 2007 in relation to language exposure influencing language production with regard to the Activation Threshold Hypothesis). However, it is likewise possible that the frequency of SG's visits may have made L2 effects on the L1 more likely as it has also been found that interaction may be more prevalent where dual activation occurs commonly (Mora, Keidel, & Flege, 2015), although it is not known how strictly German and English were separated during SG's visits to Germany.…”
Section: Discussionmentioning
confidence: 99%
“…In both fields emergence is of central importance. For example, changing degrees of observed motivational intensity (e.g., Yashima & Arano, ) and the growth and attrition of linguistic phenomena (e.g., de Leeuw, Opitz, & Lubinska, ; Opitz, ) are both understood as the emergence of novel behaviors. Similarly, in the “complexity thought modeling” (Larsen–Freeman & Cameron, , p. 41) in the current article, emergence is the base concept upon which propositions are constructed.…”
Section: Complexity Theories and Emergencementioning
confidence: 99%
“…One body of research that bears on the study of L1 perceptual attrition in early bilinguals is the literature on L2 effects in late bilinguals, which shows that L2-influenced modifications to the phonetics and/or phonology of the L1 may occur even in learners who acquire a L2 after the age of 18 (de Leeuw, 2014;de Leeuw, Opitz, & Lubińska, 2013). For example, L1 English speakers in their 20s were found to modify several aspects of their L1 production during the first weeks of immersive L2 Korean learning (Chang, 2012(Chang, , 2013b, and similar effects of L2 immersion on the acoustic properties, perceived accent, and/or phonological rule implementation of L1 production have been reported in various late-bilingual populations: L1 English-L2 Portuguese (Major, 1992), L1 Russian-L2 English (Dmitrieva, Jongman, & Sereno, 2010), L1 German-L2 English and L1 German-L2 Dutch (de Leeuw, Mennen, & Scobbie, 2012de Leeuw, Schmid, & Mennen, 2010;Hopp & Schmid, 2013;Schmid & Hopp, 2014), and L1 Dutch-L2 English (Mayr, Price, & Mennen, 2012).…”
Section: Age Effects In L1 Attritionmentioning
confidence: 99%